Der Handel von Kreditrisiken: Eine neue Dimension des Kapitalmarktes - Jan Pieter Krahnen (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2005)
This paper makes an attempt to present the economics of credit securitisation in a nontechnical way, starting from the description and the analysis of a typical securitisation transaction. The paper sketches a theoretical explanation for why tranching, or nonproportional risk sharing, which is at the heart of securitisation transactions, may allow commercial banks to maximize their shareholder value. However, the analysis makes also clear that the conditions under which credit securitisation enhances welfare, are fairly restrictive, and require not only an active role of the banking supervisory authorities, but also a price tag on the implicit insurance currently provided by the lender of last resort.
Keywords: 330; Kreditrisiko; Finanzderivat; Securitization; Wertpapierhandel